2018
DOI: 10.1021/acscatal.8b03592
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Phosphoranyl Radicals via Photoredox Catalysis Enables Voltage–Independent Activation of Strong C–O Bonds

Abstract: Despite the prevalence of alcohols and carboxylic acids as functional groups in organic molecules and the potential to serve as radical precursors, C−O bonds remain difficult to activate. We report a synthetic strategy for direct access to both alkyl and acyl radicals from these ubiquitous functional groups via photoredox catalysis. This method exploits the unique reactivity of phosphoranyl radicals, generated from a polar/SET crossover between a phosphine radical cation and an oxygen-centered nucleophile. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
128
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(131 citation statements)
references
References 36 publications
2
128
0
1
Order By: Relevance
“…In 2018, our group [5] and Doyle et al [6] have independently developed photoredox phosphoranyl radical chemistry for redox-potential independent deoxygenation of carboxylic acids. This affords ap romising route for the construction of aryl-alkyl ketones and aldehydes directly from carboxylic acids.…”
mentioning
confidence: 99%
“…In 2018, our group [5] and Doyle et al [6] have independently developed photoredox phosphoranyl radical chemistry for redox-potential independent deoxygenation of carboxylic acids. This affords ap romising route for the construction of aryl-alkyl ketones and aldehydes directly from carboxylic acids.…”
mentioning
confidence: 99%
“…Subsequently, we studied the substrate scope of aromatic bromides (Fig. 5) and found that many commercially available aromatic bromides can be used to deliver the desired ketones (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) in good yields. The excellent functional group tolerance of -COOR (28,33,44,45), -CN (29, 34), terminal unsaturated chemical bonds (43,44), and heteroarenes (38)(39)(40)(41)(42)(43)46) support the practicality of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…This could simplify and upgrade ketone synthesis from carboxylic acids and organic halides 13 . Very recently, our group and Doyle et al reported an elegant photoredoxpromoted mild deoxygenation of carboxylic acids generating acyl radicals [31][32][33][34][35] . Since photoredox and nickel-catalyzed C-O bond formation between carboxylic acids and aromatic bromides has been reported 36 to achieve the desired crosselectrophile coupling, acyl radical oxidative addition by a metallaphotoredox pathway [37][38][39][40][41] is essential to suppress the C-O bond formation (Fig.…”
mentioning
confidence: 99%
“…[14] Doyle disclosedanovel deoxygenative hydrogenation of benzylic alcohols by phosphine radical cation (Scheme 1, III). [15] Encouraged by these reports and other studies, [13,17] we envisioned that phosphine would complete such ap rocess due to strong PÀOb ond strength (148 kcal mol À1 for P(O)(OEt) 3 ). [18] Herein, we wish to report a novel deoxygenative alkylation of allyl/alkenyl sulfones from readily accessible N-alkoxyphthalimidesu nder visible light (Scheme 1, IV).…”
mentioning
confidence: 93%